Global Action Plan 1.0: Advance Targets - Abdi, Hodan (JOURNAL OF GLOBAL NEUROSURGERY, 2023)
Most global neurosurgery efforts remain geared towards clinical training. Through research, mentorship, and funding, GNC has focused heavily on expanding the neurosurgical workforce in LMICs. There remains a huge gap in funds that go towards public health training and the health system expansion. GNC continues to raise funds for global neurosurgeon training in the public health aspects of neurosurgery such as building research capacity. New global neurosurgery funds are emerging every year. New funding sources for global neurosurgery include the NOF research award, CNS and the Bassett fellowship. These resources are reliable catalysts in Increasing training and research. However, additional funding will be needed in the future as GNC initiatives become more fruitful.